2002
DOI: 10.1001/archsurg.137.12.1408
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Laparoscopic and Conventional Surgery on Kupffer Cells, Tumor-Associated CD44 Expression, and Intrahepatic Tumor Spread

Abstract: Background: The oncologic feasibility of laparoscopic surgery for the cure of colorectal cancer is under debate. The effect of laparoscopic colorectal cancer resection on hepatic tumor spread has not yet been clarified. Hypothesis: Laparoscopic surgery affects cellmediated immune response and hepatic tumor spread dependent on intraperitoneal insufflation. Methods: Thirty WAG/Rij rats were randomized into 3 operative groups: carbon dioxide (CO 2) laparoscopy (n=10), "gasless" laparoscopy (n = 10), and laparotom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
1
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 24 publications
0
17
1
2
Order By: Relevance
“…On the other hand, recent report suggests that prolonged pneumoperitoneum for about 6 hours does not hamper liver function or cause liver damage after extended laparoscopic procedures [28]. Furthermore, it is undeniable that CO 2 pneumoperitoneum induces pathophysiological hemodynamic, pulmonary, renal, splanchnic, and endocrine changes [29]. According to two papers published by Chiu AW, et al [30,31], peritoneal insufflation of CO 2 to a pressure of 15mmHg elicited transient elevations of the aortic pressure, carotid arterial blood flow, and superficial renal cortical blood flow in porcine model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, recent report suggests that prolonged pneumoperitoneum for about 6 hours does not hamper liver function or cause liver damage after extended laparoscopic procedures [28]. Furthermore, it is undeniable that CO 2 pneumoperitoneum induces pathophysiological hemodynamic, pulmonary, renal, splanchnic, and endocrine changes [29]. According to two papers published by Chiu AW, et al [30,31], peritoneal insufflation of CO 2 to a pressure of 15mmHg elicited transient elevations of the aortic pressure, carotid arterial blood flow, and superficial renal cortical blood flow in porcine model.…”
Section: Discussionmentioning
confidence: 99%
“…Ishida et al [14] demonstrated that an elevated insufflation pressure facilitates the location of intraportally injected tumor cells in the liver, and that the pulmonary location of the tumor cells may not depend on insufflation pressures. It has been reported that CO 2 gas or acidosis itself inhibits phagocytosis by macrophages in the abdominal cavity, and that the ability to phagocytose intraoperative free tumor cells may be suppressed [14,29].…”
Section: Discussionmentioning
confidence: 99%
“…Previous applications of the CC531s model in experimental laparoscopy were performed by intrasplenic 7 or intraportal 8,9 injection of the tumour cells, leading to multiple hepatic metastases after haematogeneous spread. In contrast, CC531s cells were injected subcapsularly in a nonsurgical oncological study to induce well-localised and accessible liver metastases.…”
Section: Discussionmentioning
confidence: 99%
“…A couple of experimental studies have assessed the influence of laparoscopy on postoperative outcome of colorectal carcinoma using various models. The assessment of haematogeneous hepatic tumour spread in rats 7,8 and mice 9 and of renal or cutaneous tumour growth after subcapsular 10 or subcutaneous 11 injection of colorectal carcinoma cells have led to controversial for and against arguments for the laparoscopic technique. Importantly, hepatic macrophages have been described as playing a key oncological role in cellular antitumoural defence in respect of enhanced experimental tumour growth following selective depletion of phagocytotic cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation